Can Palisade and Guinea Grass Sowing Time in Intercropping Systems Affect Soybean Yield and Soil Chemical Properties? - Costa, Nídia Raquel; Andreotti, Marcelo; Crusciol, Carlos Alexandre Costa; Pariz, Cristiano Magalhães; Bossolani, João William; Castilhos, André Michel de; Nascimento, Carlos Antonio Costa do; Lima, César Gustavo da Rocha; Bonini, Carolina dos Santos Batista; Kuramae, Eiko Eurya (Frontiers in Sustainable Food Systems, 2020)
In tropical regions, intercropping systems under no-tillage improve biomass quantity, soil conservation, and cash crop productivity. However, the optimal sowing time for forage species in these cropping systems is unknown. The objective of this study was to evaluate the effects of two sowing times of palisade and guinea grass on forage production and quality, soybean yield and soil chemical properties. Palisade and guinea grasses were sown for intercropping with maize or after maize silage harvest (hereafter succession) in an experiment carried out over three crop seasons. We evaluated forage dry matter production, pasture nutritive values, straw nutrient content, soybean leaf nutrients, yield, and soil fertility. The highest dry matter production was 8.1 Mg ha−1 for guinea grass in the intercropping system (sum of 3 cuts). Sowing forage after maize silage harvest provided 4% more crude protein compared with intercropping, regardless of grass species. Soybean yield was over 1.0 Mg ha−1 higher when soybean was cropped in succession compared with intercropping; however, the effects of the two forage grasses on soybean production were similar. Soil pH, calcium and magnesium content, cation exchange capacity, and base saturation were higher in the intercropping systems than in the succession systems, particularly when guinea grass was cultivated. Sowing guinea grass after maize harvest provided better forage quality, nutrient cycling, soybean yields, and soil chemical properties in tropical conditions.